ENHANCING SPEAKING SKILL THROUGH YOUTUBE: SYSTEMATIC LITERATURE REVIEW - Suseno, Edy; DARMA, IKIP WIDYA (Innovare Journal of Social Sciences, 2024)
Speaking is the most important part of communication. Many students in universities, junior high schools, and senior high schools have trouble conveying their ideas to others. Using YouTube to help students ease their ability to practice speaking is promising. Eleven articles showed that kind of notion. They were found on the Google Scholar website. Filtering them by the keyword “learning to speak through YouTube” and the year setting “since 2018” has determined that they are appropriate to be analyzed. All articles adapted method designs such as qualitative, quantitative, and mixed-method approaches differently. The analysis done by each article showed the effectiveness of using YouTube to enhance speaking ability. This kind of finding could be used by teachers to teach the related subject. It also triggers other researchers to do related studies.